1994
DOI: 10.1111/j.1532-5415.1994.tb06535.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Physical Performance and Mobility Examination

Abstract: The PPME is a reliable and valid performance-based instrument measuring physical functioning and mobility in hospitalized and frail elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 28 publications
1
72
0
3
Order By: Relevance
“…It has been reported that the ability level of movement activity decreases with age, and that it significantly relates to comprehensive ADL ability level [19][20][21] . Lower limb activities representing movement activity are considered to be important assessment tools even in healthy older people.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the ability level of movement activity decreases with age, and that it significantly relates to comprehensive ADL ability level [19][20][21] . Lower limb activities representing movement activity are considered to be important assessment tools even in healthy older people.…”
Section: Discussionmentioning
confidence: 99%
“…The physical performance and mobility examination (PPME) was developed to fill the need for a performance measure of physical functioning and mobility appropriate for hospitalized and frail elders [51]. Tasks were selected that could be safely and reliably administered at the bedside, office, or home by non-professionals after brief training.…”
Section: Physical Performance and Mobility Examinationmentioning
confidence: 99%
“…It is considered that the PD who could walk without assistance was particularly superior in ADL ability level compared to the others. Winograd et al (1994) indicated the importance of mobility assessment, and developed the mobility examination (ME). They reported that as a result of examining the correlations between ME score and two ADL scores using a basic ADL index (Katz et al, 1970) and an instrumental ADL index (Lawton and Brody, 1969), significant relationships were found between mobility level and ADL ability.…”
Section: Discussionmentioning
confidence: 99%
“…Except for walking activity in G1 and G2, all domain scores are significantly correlated to overall score in all groups. Winograd et al (1994) reported that one-fifth to onethird of older hospitalized patients are dependent, one-fifth to one-third of community-dwelling elders reported difficulty walking, and more than one-third of men and half of women over age 85 reported difficulty walking up 10 steps. In Japan, it is also reported that 80% of older hospitalized patients are dependent (Takeda et al, 1994).…”
Section: The Relationships Between Adl Domain Scores and Overall Scorementioning
confidence: 99%
See 1 more Smart Citation